Mediating Role of Work Motivation in the Relationship Between Work Culture and Employee Performance - Yulia Sari Fadila; Rahmisyari; Arifin (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of work culture on employee performance and assess the mediating role of work motivation in the Civil Service (ASN) of the North Gorontalo Regency Government. The method used is a quantitative approach through a survey of 120 respondents using stratified random sampling. Data analysis was performed using PLS-SEM with 5,000 subsample bootstrapping and Sobel's test to examine indirect effects. The results showed that work culture had a positive and significant effect on work motivation (t = 2.69; p = 0.007) and employee performance (t = 4.79; p = 0.000). Work motivation also has a significant effect on employee performance (t = 7.04; p = 0.000). Mediation testing shows that work motivation partially mediates the relationship between work culture and employee performance, with a z-Sobel value of 2.79 and p = 0.005. These results prove that work culture not only directly affects performance but also increases work motivation. This study confirms that strengthening work culture and developing motivation are key strategies in improving civil servant performance and provides an empirical basis for local governments to design more effective policies for improving bureaucratic performance.